2011
DOI: 10.1021/ol102858u
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) 1,2,3-Triazol-5-ylidene Complexes as Efficient Catalysts for Click Reactions of Azides with Alkynes

Abstract: Complexes of copper with 1,4-diphenyl, 1,4-dimesityl, and 1-(2,6-diisopropylphenyl)-4-(3,5-xylyl)-1,2,3-triazol-5-ylidene (abnormal NHC = N-heterocyclic carbene) were prepared by consecutive treatment of the corresponding azolium salts with silver oxide and copper chloride. The new CuCl(aNHC) complexes efficiently catalyzed click reactions of azides with alkynes to give 1,4-substituted 1,2,3-triazoles in excellent yields at room temperature with short reaction times. CuCl(TPh) was particularly effective for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(74 citation statements)
references
References 33 publications
0
74
0
Order By: Relevance
“…It is interesting to note that copper complexes comprising bulky carbene ligands (1,2,3-triazol-5-ylidenes akin to 3 or imidazol-2-ylidnes) were reported to show excellent catalytic activity in this reaction. 9a,21 Indeed,105 when using complex 3a as catalyst precursor, full conversion was observed with the same time frame as for the 2a/CuCl mixture. In light of these results we are not confident in attributing the catalytic activity to the carbene complex 3a.…”
mentioning
confidence: 77%
“…It is interesting to note that copper complexes comprising bulky carbene ligands (1,2,3-triazol-5-ylidenes akin to 3 or imidazol-2-ylidnes) were reported to show excellent catalytic activity in this reaction. 9a,21 Indeed,105 when using complex 3a as catalyst precursor, full conversion was observed with the same time frame as for the 2a/CuCl mixture. In light of these results we are not confident in attributing the catalytic activity to the carbene complex 3a.…”
mentioning
confidence: 77%
“…Two distinct mechanistic pathways that proceed through a copper(III) metallacycle or by direct π-activation of the starting iodoalkyne are likely to be competitive with these catalysts [112a]. Other carbene ligands that were recently used with success in catalysis of click reactions include abnormal N-heterocyclic carbenes (aNHCs) [55,114], mesoionic carbenes (MIC) and ring-expanded carbenes (RE-NHCs) [115]. With copper(I) complexes of triazolylidene ligands (Fig.…”
Section: Cuaacmentioning
confidence: 99%
“…The discovery of the copper-catalyzed alkyne/azide cycloaddition ("click" chemistry) [1] earlier this century has clearly advanced the research of 1,2,3-triazoles and made these five-membered heterocycles among the "hottest" compounds in chemistry-, [2] materials-, [3] and biological [4] research during the last decade.…”
Section: On the Occasion Of The 10th Anniversary Of Click Chemistrymentioning
confidence: 99%
“…
On the occasion of the 10th anniversary of click chemistryThe discovery of the copper-catalyzed alkyne/azide cycloaddition ("click" chemistry) [1] earlier this century has clearly advanced the research of 1,2,3-triazoles and made these five-membered heterocycles among the "hottest" compounds in chemistry-, [2] materials-, [3] and biological [4] research during the last decade.[5] This robust method has been widely applied to various areas as an efficient strategy for combining different functionalities under mild conditions. Recently, driven by the great success of the synthesis of 1,2,3-triazoles, more attentions have been put into investigating the fundamental reactivity of this interesting heterocycle.

[6] Various attractive applications have been reported that are associated with the unique 1,2,3-triazole core structure, including the formation of carbene intermediates [7] and adjusting the transition metal reactivity with triazole ligands.

[8] These studies further extended the versatility of 1,2,3-triazole building blocks.

…”
mentioning
confidence: 99%